The Influence Of Lifestyle And Self-Control On The Consumptive Behavior Of Shopee Paylater Users In Context of Shariah Accounting Principles - Sri Muliyani Ramli; Rezki Fani; Andi Bahri S; Trian Fisman Adisaputra (PT. Maju Malaqbi Makkarana, 2026)
This study is motivated by the rapid development of digital financial services, particularly Shopee PayLater, which has the potential to increase consumerist behaviour among students. This phenomenon requires examination not only from economic and psychological perspectives, but also from the perspective of Islamic accounting, which emphasises balance and control over consumption. This study aims to analyse the influence of lifestyle and self-control on the consumer behaviour of Shopee PayLater users and to test the role of Islamic accounting principles as a moderating variable. This study employs a quantitative approach. Data were collected via a Likert-scale questionnaire distributed to students and analysed using Partial Least Squares-based Structural Equation Modelling (SEM-PLS) with the SmartPLS application version 4.1.1.6. The results indicate that lifestyle has a positive and significant influence on consumer behaviour, whilst self-control does not have a significant influence. Sharia accounting principles have a direct and significant influence on consumptive behaviour, but are unable to moderate the relationship between lifestyle or self-control and consumptive behaviour. These findings suggest that consumer behaviour is influenced more by external factors such as lifestyle and the convenience of digital services than by internal factors within the individual, and indicate that Sharia values have not yet been fully integrated into everyday life.